Patterning of mammalian heterodont dentition within the upper and lower jaws. Issue 2 (March 2015) - Yamanaka, Atsushi; Iwai, Haruki; Uemura, Masanori; Goto, Tetsuya
SUMMARY: Mammalian heterodont dentition is differentiated into incisors, canines, premolars, and molars in the mesial–distal direction, in both the upper and lower jaws. Although all the lower teeth are rooted in the mandible, the upper incisors are rooted in the premaxilla and the upper canine and the teeth behind it are in the maxilla. The present study uncovers ontogenetic backgrounds to these shared and differing mesiodistal patterns of the upper and lower dentition. To this end, we examined the dentition development of the house shrew, Suncus murinus, instead of the rodent model animals because the dentition of this primitive eutherian species includes all the tooth classes, and no toothless diastema region. In the shrew, the upper incisor‐forming region extended over the medial nasal prominence and the mesial part of the maxillary prominence. Consequently, the maxillary and mandibular prominences were in a mirror‐image relationship in terms of the mesiodistally differentiated tooth‐forming regions and of the complementary gene expression pattern, with Bmp4 in the mesial and Fgf8 in the distal regions. This suggests shared molecular mechanisms regulating tooth class differentiation between the upper and lower jaws. However, the premaxillary bone appeared within the mesenchyme of the medial nasal prominence, but grew distally beyond the former epithelial boundary with the maxillary prominence to form, finally, the incisive (premaxillary–maxillary) suture just mesial to the canine. Therefore, the developmental locations of the upper incisors are not inconsistent with the classical osteological criterion of the upper canine by comparative odontologists.